New aspects of microcurrent electrical neuromuscular stimulation in sports medicine - Hiroto Fujiya; Katsumasa Goto (Japanese Society of Physical Fitness and Sports Medicine, 2016)
Sports-associated injuries often involve trauma to soft tissues such as ligaments, tendons, skeletal muscle, and skin. A shortened recovery process for injured tissues is of great interest to athletes, as injury-associated inactivity depresses both sports performance and physical fitness. Recently proposed treatments to accelerate tissue repair include microcurrent electrical neuromuscular stimulation (MENS), low-intensity pulsed ultrasound (LIPUS), hyperbaric oxygen (HBO), and autologous platelet-rich plasma (PRP). Among these treatments, MENS has been applied to alleviate pain and reduce swelling following sports-associated injuries of tendons and ligaments. MENS is reported to stimulate the regeneration of skeletal muscles, a part of the body commonly injured in sports. MENS is expected to soon become a standard therapy for accelerating the repair of injured skeletal muscles and other soft tissues. In this review, we provide an overview of MENS and briefly describe several other proposed treatments for sports-associated injuries.